Induksi Tetraploid Pada Tanaman Jambu Biji Merah (Psidium guajava L.) secara In Vitro - Handayani, Tri; Witjaksono, Witjaksono; Nugraheni, K. Utami (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTSome commercial varieties of Guava seedless are triploid and rarely found naturally. A triploid variety with less seeds and better yield potential can be achieved by crossing tetraploid to diploid variety. Guava tetraploid plants can be synthetically induced by using oryzalin or colchicine to double the chromosome from its diploid. This research was aimed to obtain tetraploid lines by studying the effects of oryzalin in germination and in vitro growth of Guava. Seed from Red Guava were cultured in liquid medium MS + 2 mgL-1 BA with adding oryzalin according to the treatment, then seed planted in MS solid medium. Seed explants were exposed to Oryzalin 0 (controls), 15, 30 dan 60 ?M with exposure time are 23, 36 and 49 days or 3, 5, and 7 weeks. Results from polyploid induction were 8 tetraploid (5.48%) and 9 (6.16%) mixoploid shoots in vitro. High est tetraploid shoots were obtained from treatments by exposing the seed explant to 15 â 30 ?M oryzalin for 23 â 36 days. Oryzalin treatments inhibit germination and in vitro growth of Guava until 1st subculture. After second subculture, tetraploid or mixoploid shoots quantitatively showed no difference respons on in vitro growth with its diploid.Keywords: guava, tetraploid, seed explant, in vitro germination, polyploid